Profitabilitas, Likuiditas, Ukuran Perusahaan dan Nilai Perusahaan - Damayani, Kadek Asri; Wirawati, Ni Gusti Putu (E-Jurnal Akuntansi, 2022)
The purpose of this study was to determine the effect of liquidity, profitability, and firm size on firm value. This study uses real estate and property companies from 2017-2019 listed on the Indonesia Stock Exchange as the population in this study. The method of determining the sample using purposive sampling technique. The number of research samples was 28 companies with an observation period of 3 years, resulting in 84 samples of observations. The hypothesis in this study was tested using multiple linear regression analysis techniques. The results of the analysis show that profitability, liquidity and firm size have a positive effect on the value of the property and real estate sector companies. So it can be concluded that profitability, liquidity and company size play an important role in determining the value of companies in the property and real estate sectors. Keywords : Profitability; Liquidity; Firm Size; Firm Value.